Strain-specific effect on biphasic DNA binding by HIV-1 integrase. (1st March 2019) - Hill, Kyle J.; Rogers, Leonard C.; Njenda, Duncan T.; Burke, Donald H.; Sarafianos, Stefan G.; Sönnerborg, Anders; Neogi, Ujjwal; Singh, Kamalendra
Abstract : N/A: The oligomerization of HIV-1 integrase onto DNA is not well understood. Here we show that HIV-1 integrase binds the DNA in biphasic (high-affinity and low-affinity) modes. For HIV-1 subtype B, the high-affinity mode is ∼100-fold greater than the low-affinity mode ( K d .DNA  = 37 and 3400 nmol/l, respectively). The K d .DNA values of patient-derived integrases containing subtype-specific polymorphisms were affected two- to four-fold, suggesting that polymorphisms may have an influence on effective-concentrations of inhibitors, as these inhibitors preferably bind to integrase-DNA complex.